Transcontinental to acquire Canadian assets of Quad/Graphics and to sell its Mexican assets (Canada NewsWire, 2011)
MONTREAL, July 13, 2011 /CNW Telbec/ - Transcontinental Inc. (TSX: TCL.A, TCL.B, TCL.PR.D) and Quad/Graphics Inc. (NYSE: QUAD) have entered into a definitive agreement pursuant to which Transcontinental will indirectly acquire all the shares of Quad Graphics Canada Inc. In a separate transaction, Transcontinental has also reached an agreement to sell its Mexican operations as well as transfer its black and white book printing business, destined for U.S. export, to Quad/Graphics. The definitive agreement has been approved by the Boards of Directors of both Transcontinental and Quad/Graphics. The transactions are subject to obtaining regulatory clearances, including under the Canadian Competition Act and the Mexican Federal Law on Economic Competition. Essentially, these transactions represent an exchange of assets. Both transactions are expected to close in the fall. "The acquisition of the Canadian assets of Quad/Graphics is in line with our strategy to build on our more traditional print assets and is key to maintain a solid business going forward given the competitive and industry dynamics. It will allow us to leverage the over $700 million in investments we have made to our printing platform over the last several years. These transactions combined will generate at least $40 million in net incremental EBITDA for Transcontinental, over 12 to 24 months following the closure of the transactions," said Francois Olivier, President and Chief Executive Officer. "The print markets in general have suffered from overcapacity and more intense competitive pressures in certain niches in recent years, with the proliferation of digital and web communication platforms, technological advances in new printing presses as well as the entry of U.S. players in the Canadian marketplace. These transactions will permit us to improve our capacity utilization rate and better equip us to face these new challenges," continued Mr. Olivier. "We thank all the employees in our Mexican operations for their dedication and outstanding contribution to the company's success," concluded Mr. Olivier.